A Review of Full-Body Radiography in Nontraumatic Emergency Medicine - S. P. Whiley; G. Mantokoudis; D. Ott; H. Zimmerman; A. K. Exadaktylos (Emergency Medicine International)
This paper reports on the application of full-body radiography to nontraumatic emergency situations. The Lodox Statscan is an X-ray machine capable of imaging the entire body in 13 seconds using linear slit scanning radiography (LSSR). Nontraumatic emergency applications in ventriculoperitoneal (VP) shunt visualisation, emergency room arteriography (ERA), detection of foreign bodies, and paediatric emergency imaging are presented. Reports show that the fast, full-body, and low-dose scanning capabilities of the Lodox system make it well suited to these applications, with the same or better image quality, faster processing times, and lower dose to patients. In particular, the large format scans allowing visualisation of a greater area of anatomy make it well suited to VP shunt monitoring, ERA, and the detection of foreign bodies. Whilst more studies are required, it can be concluded that the Lodox Statscan has the potential for widespread use in these and other nontraumatic emergency radiology applications.